On the Soviet Foreign Policy (Czech Journal of International Relations, 1967)
The authors of the book "History of Foreign Policy of the USSR" are prominent Soviet workers in the field of international relations and diplomacy who worked under the leadership of B. N. Ponomarev, A. A. Gromyk and V. M. Chvostov. I see the messengers of this book in that it enabled the Soviet people to understand more deeply the essence of the foreign policy of the USSR, and the Ctenari foreign policy embraced the goals of this policy.I define Soviet foreign policy as a policy that harmoniously combines the national interests of the Soviet state and the Soviet people with the international obligations of the working class that seized power. The authors divided the history of Soviet foreign policy into two basic stages. Proni begins with the Great Rhine Socialist Revolution and the year 1945, the second stage begins with the consolidation of the results of the USSR's struggle against fascism, the victory of the people's revolutions in Europe and Asia, and the emergence of the world socialist system.